ADMINISTRACIÓN Y CAPACITACIÓN DE LOS INGENIEROS EN LAS TÉCNICAS DE LA INVESTIGACIÓN FORENSE, EN EL DEPARTAMENTO DE INGENIERÍA FORENSE DE LA DIRECCIÓN DE CRIMINALÍSTICA DE LA POLICÍA NACIONAL DEL PERÚ - Ramos Huamán, Julio César (2016)
There is a need to administer and train Engineers of different specialties in Forensic Investigation techniques, a field unknown to them, since there is no subject in the curriculum of the Engineering Faculties, of any University of the Peruvian university system, a subject called "Forensic Engineering", "Legal Engineering" or "Judicial Engineering"; that prepares the Engineer in the forensic field. The Forensic Engineer must be trained to apply their knowledge in the investigation of a criminal act, contributing their knowledge through objective evidence and in this way supporting the administration of justice (supports the police investigation, and justice operators in the field criminalistic). As criminology is a multidisciplinary science, which investigates the way in which the dynamics of crime have developed, in search of the truth, it is necessary to use all kinds of scientific knowledge, especially from all branches of engineering to clarify a criminal fact . Therefore, a forensic engineer must be a good administrator and knowledgeable of forensic techniques, whose purpose is to find the truth through technical-scientific evidence (objective evidence). This investigation made it possible to determine that training is really a factor that significantly influences the identification of Forensic Engineering by the Engineers who provide services in the PNP Criminalistics Directorate; Therefore, it is necessary for the different training programs to be implemented according to the needs of the organization, which will directly affect the service provided by these professionals.